2015
DOI: 10.5194/cp-11-233-2015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Mediterranean circulation and water characteristics due to restriction of the Atlantic connection: a high-resolution ocean model

Abstract: Abstract. A high-resolution parallel ocean model is set up to examine how the sill depth of the Atlantic connection affects circulation and water characteristics in the MediterraneanBasin. An analysis of the model performance, comparing model results with observations of the present-day Mediterranean, demonstrates its ability to reproduce observed water characteristics and circulation (including deep water formation). A series of experiments with different sill depths in the Atlantic-Mediterranean connection i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 80 publications
1
19
0
1
Order By: Relevance
“…1,5 & 6). In order to investigate the gateway dimension problem, Topper and Meijer (2015) used a regional ocean model to examine how a restricted Mediterranean-Atlantic connection would influence both Mediterranean thermohaline circulation and water properties. This study indicates that Mediterranean-Atlantic exchange is proportional to sill depth and the results of these simulations can therefore be used to interpret the Late Miocene sedimentary record both preceding and during the MSC Topper and Meijer (2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5 & 6). In order to investigate the gateway dimension problem, Topper and Meijer (2015) used a regional ocean model to examine how a restricted Mediterranean-Atlantic connection would influence both Mediterranean thermohaline circulation and water properties. This study indicates that Mediterranean-Atlantic exchange is proportional to sill depth and the results of these simulations can therefore be used to interpret the Late Miocene sedimentary record both preceding and during the MSC Topper and Meijer (2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Sill depths below 10 m result in blocked Mediterranean Outflow, which could represent a plausible scenario for the second stage of the MSC (Fig. 2), characterised by the rapid accumulation of halite in the Mediterranean (Topper and Meijer, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…First, variability within a precessional cycle remains difficult to resolve. Lourens et al () observed a ~3‐ky lag from precession minima to the midpoint of youngest Eastern Mediterranean sapropel S1 based on 14 C dating; similarly, Topper and Meijer () found that responses in a “typical” marginal Mediterranean basin may lag precession minima by ~3 ka. However, Weber and Tuenter () describe general circulation model results indicating there should be little to no time lag for precessional climate forcing at midlatitudes.…”
Section: Discussionmentioning
confidence: 88%
“…First, variability within a precessional cycle remains difficult to resolve. Lourens et al (1996) observed a~3ky lag from precession minima to the midpoint of youngest Eastern Mediterranean sapropel S1 based on 14 C dating; similarly, Topper and Meijer (2015) found that responses in a "typical" marginal Mediterranean basin may lag precession minima by~3 ka. However, Weber and Tuenter (2011) The leads and lags observed from data-based studies are partly due to the complex processes mediating sapropel deposition, the fact that these may not be identical in all parts of the Mediterranean region, and post-depositional changes.…”
Section: Potential Role Of Seawater Pb Isotopes In Mediterranean Astrmentioning
confidence: 88%
“…For brevity, we will refer to the i direction as “east‐west” and j direction as “north‐south.” Starting with Zavatarelli and Mellor [], POM has been widely applied to investigate the oceanography of the Mediterranean Sea. Recently, sbPOM has been successfully used to study the Mediterranean circulation [ Topper and Meijer , ].…”
Section: Model Setupmentioning
confidence: 99%